Severe acute respiratory syndrome coronavirus 2 virus-like particles induce dendritic cell maturation and modulate T cell immunity - Mi, Youjun; Liang, Lijuan; Xu, Kun; Li, Qing; Wang, Wenting; Dang, Wenrui; Deng, Jiahui; Zhi, Yucheng; Li, Xuefeng; Tan, Jiying (Frontiers in Cellular and Infection Microbiology, 2022)
Dendritic Cells (DCs) are professional antigen-presenting cells and play a pivotal role in both innate and acquired immune responses to pathogens. However, the role of DCs in the Coronavirus Disease 2019 (COVID-19) and vaccine have unclarified. Virus-like particles (VLPs) structurally mimic the authentic virus which was one of candidate vaccines. In this study, we intended to use SARS-CoV-2 VLPs as an alternative to study the interaction of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) with DCs. The results shows that SARS-CoV-2 VLPs induces DCs maturation by augmenting the expression of cell surface molecules (CD80, CD86, and MHC class II) and inflammatory cytokine production (TNF-α, IL-1β, IL-6, and IL-12p70) in DCs on mitogen-activated protein kinases (MAPK), and nuclear factor-κB (NF-κB) signaling pathways. In addition, mature DCs induced by SARS-CoV-2 VLPs promote T cell proliferation, moreover this proliferation is dependent on the concentration of VLPs. Our results indicate that SARS-CoV-2 VLPs regulate immunity by interacting with DCs, and these findings will help us better understanding pathogenesis of SARS-CoV-2 or to design vaccine of SARS-CoV-2.